FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN DI RESTURANT ALPHA HOTEL PEKANBARU - Maria Devita; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Performance is the performance of work or work of a worker, and employee performance is a quality result achieved by an employee in performing their duties in accordance with the responsibilities given to him, and This study aims to determine what factors affect the employee's performance in alpha restaurant hotel pekanbaru. And what factors become the dominant factors affect employee performance in alpha hotel restaurant pekanbaru. Factors discussed in this case are individual factors, organizational factors and management factors. This research was conducted from April to August 2017 and located in restaurant alpha hotel pekanbaru. This research design using quantitative method with descriptive approach. Based on the results of research that has been done, that the three factors above do affect employee performance at alpha hotel restaurant Pekanbaru, that is individual factor of organization factor and management factor. And the most dominant factor affecting employee performance in alpha hotel restaurant pekanbaru is individual factor, the need for compensation. Keywords: performance, factors and hotel employees